Analysis of CYP27A1 mutations in Han Chinese women with intrahepatic cholestasis of pregnancy. (12th December 2022) - Xin, Siming; Liu, Xianxian; Liu, Huai; Zeng, Xiaoming; Xiong, Ying; Zhou, Mengni; Zou, Yang; Zeng, Yang; Zheng, Jiusheng; Lai, Hua
Abstract: Objective: To explore the cytochrome P450 family 27 subfamily A member 1 (CYP27A1) gene mutations in Chinese women with intrahepatic cholestasis of pregnancy (ICP) and the correlation between CYP27A gene mutations and BA (bile acid) level changes. Methods: In this study, the entire coding region of the CYP27A1 gene was sequenced in 151 Han Chinese women with ICP and 1029 matched samples, and the pathogenicity of identified CYP27A1 gene mutations was judged through evolutionary conservation analysis, computational analysis and protein structure modeling. Finally, we verified the relationship between gene mutations and total serum bile acid (TBA) and cholesterol (CHOL) levels through experiments in cell culture. Results: We identified five heterozygous CYP27A1 missense mutations in five ICP samples. Three online tools, Polyphen-2, MutationTaster and SIFT, predicted that the five CYP27A1 mutations were pathogenic. Furthermore, all five mutations caused marked protein structural changes. Experiments in cells showed that the intracellular and medium levels of TBA in the mutant groups were lower than those in the wild-type group, while the CHOL levels were higher in all mutants except for the R158H mutant. Conclusions: CYP27A1 mutations are associated with the levels of TBA and CHOL, suggesting that CYP27A1 mutations contribute to abnormal total cholesterol and BA levels, which leads to ICP.